Management of dental office during COVID-19 Pandemic - Kalidindi, Sri Sowmya; Ravi Kumar, C; Sujesh, M; Lukka, Pavani (International Journal of Dental Materials, 2021)
Novel Coronavirus (COVID-19) is a deadly protein molecule devastating the humankind and has brought down the life to a standstill. Its effect is determined by the interaction among the agent, the host and the environment. The proven fact that the spread of COVID-19 is air-borne has made it mandatory for the dental fraternity to follow a systematic protocol in clinical practice. A proper history of travel and exposure, thermal scanning, symptoms of sore throat, dry cough and difficulty in breathing makes you suspect an individual with COVID-19. It is imperative to consider only emergency and essential dental procedures to be carried out under strict aseptic measures, not only for suspects but also for routine patients. COVID-19 and dentistry are very closely related to each other as dental professionals are directly working in the oral cavity. Although the Ministry of Health & Family Welfare has issued comprehensive guidance to prevent the occurrence of hospital-acquired infection (HAI) in health facilities, the practice of universal precautions might still be lacking in many dental professionals due to improper knowledge. Data acquisition was carried out using the keywords, COVID-19, control of infection, and patient management in dental offices in PubMed, Medline, ProQuest, etc., electronic databases. There was also a manual scan of many journals and books, and highly relevant papers were considered for the present study.